Model for Bacteriophage T4 Development in Escherichia coli - Rabinovitch, Avinoam (American Society for Microbiology, 1999)
Mathematical relations for the number of mature T4 bacteriophages, both inside and after lysis of an Escherichia coli cell, as a function of time after infection by a single phage were obtained, with the following five parameters: delay time until the first T4 is completed inside the bacterium (eclipse period, ν) and its standard deviation (ς), the rate at which the number of ripe T4 increases inside the bacterium during the rise period (α), and the time when the bacterium bursts (μ) and its standard deviation (β). Burst size [B = α(μ − ν)], the number of phages released from an infected bacterium, is thus a dependent parameter. A least-squares program was used to derive the values of the parameters for a variety of experimental results obtained with wild-type T4 in E. coli B/r under different growth conditions and manipulations (H. Hadas, M. Einav, I. Fishov, and A. Zaritsky, Microbiology 143:179–185, 1997). A “destruction parameter” (ζ) was added to take care of the adverse effect of chloroform on phage survival. The overall agreement between the model and the experiment is quite good. The dependence of the derived parameters on growth conditions can be used to predict phage development under other experimental manipulations.